Interpersonal Violence and Mental Health Outcomes: Mediation by Self-efficacy and Coping. Issue 2 (17th February 2022) - Magalhães, Eunice; Grych, John; Ferreira, Célia; Antunes, Carla; Prioste, Ana; Jongenelen, Inês
ABSTRACT: There is a compelling need to explore the mechanisms linking violence to mental health. This study tested the mediating role of self-efficacy and coping in the association between victimization and mental health. Data were obtained from 422 adults (aged 18-77; M = 30.05; SD = 10.93). Self-efficacy and maladaptive coping strategies mediated the association between physical victimization and anxiety, and the association between psychological victimization and satisfaction with life anxiety and depression. Self-efficacy and adaptive coping also mediated the association between psychological victimization and satisfaction with life. This study provides important implications for research and practice.